2018
DOI: 10.1530/ec-18-0250
|View full text |Cite
|
Sign up to set email alerts
|

Management of prolactinoma: a survey of endocrinologists in China

Abstract: ObjectiveTo assess the current management of prolactinoma among endocrinologists in China.MethodsAn online survey of a large sample of endocrinologists was conducted in China. The questionnaire included 21 questions related to controversial issues about the management of prolactinomas. Doctors in the endocrinology department of a university-affiliated hospital or a comprehensive secondary hospital in 12 cities from East, West, South, North and Middle China were surveyed.ResultsA total of 290 valid questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
1
0
1
Order By: Relevance
“…Анкеты охватывали различные аспекты диагностики и лечения пролактином и ГПРЛ [4][5][6][7]. Всего 22-30% респондентов считали, что уровень пролактина (ПРЛ)<2000 мЕд/л исключает наличие пролактиномы.…”
Section: онлайн-опросы по гпрл врачей из разных странunclassified
“…Анкеты охватывали различные аспекты диагностики и лечения пролактином и ГПРЛ [4][5][6][7]. Всего 22-30% респондентов считали, что уровень пролактина (ПРЛ)<2000 мЕд/л исключает наличие пролактиномы.…”
Section: онлайн-опросы по гпрл врачей из разных странunclassified
“…Table 1 lists the studies (n = 19) that were excluded along with the reason for exclusion [ Table 1 ]. [ 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] Finally, eight (n = 8) studies were included in this scoping review. [ 34 35 36 37 38 39 40 41 ] Characteristics of all the studies[ 34 35 36 37 38 39 40 41 ] are shown in Table 2 .…”
Section: R Esultsmentioning
confidence: 99%